Are self-employed really happier than employees? An approach modelling adaptation and anticipation effects to self-employment and general job changes - Dominik Hanglberger; Joachim Merz (Institute for the Study of Labor (IZA), 2011)
Empirical analyses using cross-sectional and panel data found significantly higher levels of job satisfaction for self-employed than for employees. We argue that those estimates in previous studies might be biased by neglecting anticipation and adaptation effects. For testing we specify several models accounting for anticipation and adaptation to self-employment and job changes. Based on data from the German Socio-Economic Panel Survey (SOEP) we find that becoming self-employed is associated with large negative anticipation effects. In contrast to recent literature we find no specific long term effect of self-employment on job satisfaction. Accounting for anticipation and adaptation to job changes in general, which includes changes between employee jobs, reduces the effect of self-employment on job satisfaction by 70%. When controlling for anticipation and adaptation to job changes, we find no further anticipation effect of self-employment and a weak positive but not significant effect of self-employment on job satisfaction for three years. Thus adaptation wipes out higher satisfaction within the first three years being self-employed. According to our results previous studies at least overestimated possible positive effects of self-employment on job satisfaction.
urn:nbn:de:101:1-201104134329
Keywords: J23; J28; J81; 330; job satisfaction; self-employment; hedonic treadmill model; adaptation; anticipation; fixed-effects panel estimations; German Socio-Economic Panel (SOEP); Selbstständige; Arbeitszufriedenheit; Erwerbsverlauf; Schätzung; Deutschland